Keabsahan Perkawinan Beda Agama dalam Perspektif Hukum Islam di Indonesia Berdasarkan Putusan Pengadilan Nomor 91/Pdt.P/2022/PN BKS - Ekky Adityawan; Irdanuraprida Idris (IAI Nasional Laa Roiba Bogor, 2026)
The phenomenon of interfaith marriages in Indonesia is understood through observations of primary and secondary legal materials. Marriage is often viewed by Indonesian society as a union between an adult man and an adult woman, conducted according to religious teachings and valid law, with the intention of establishing a new family and household. The unification of marriage law in Indonesia is contained in Law Number 1 of 1974 concerning Marriage, as amended by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. Ironically, this unification of marriage law does not regulate interfaith marriages; the validity of a marriage is left to the laws of each individual's religion and beliefs. Those of different religions who still refuse to marry according to the laws of their chosen religion face difficulties because the norms are void. This research will address two research questions: 1. What is the perspective of Islamic law and does positive law on marriage in Indonesia encompass interfaith marriages? 2. What is the legality of interfaith marriages in Indonesia, from an Islamic legal perspective, in Decision Number 91/Pdt.P/2022/Pn Bks? The research method used is normative legal research, utilizing secondary data in the form of primary, secondary, and tertiary legal materials. The results indicate that, in principle, positive law governing marriage does not regulate interfaith marriages, yet interfaith marriages still frequently occur, creating difficulties in obtaining legal legitimacy. An application to conduct an interfaith marriage was filed with the Bekasi District Court. In conclusion, positive law governing marriage does not extend to interfaith marriages, while from an Islamic legal perspective, interfaith marriages are prohibited. An interfaith marriage in the case aquo is valid if the marriage is conducted according to the Christian religion, as stated in the Indonesian Christian Ordinance (S 1933 Number 74).